Colony-Forming and Cell Viability Assay to Assess Nanotoxicity of Maleic Acid and N-vinyl Caprolactam-Based Nanoarchitectures - Bekar Buse; Akar Burcu; Akan Handan Sevim; Can Hatice Kaplan (The EuroBiotech Journal)
Organo-montmorillonite (Org-MMT) is a widely used silicate in polymer nanotechnology, enhancing the durability of nanocomposites by improving polymer strength and thermal stability. This study evaluates the anticancer effects of poly(maleic anhydride-alt-N-vinyl caprolactam) [poly(MA-alt-VCL)]-Org-MMT nanocomposites synthesized with varying clay concentrations. The cytotoxicity of Org-MMT, poly(MA-alt-VCL), and their nanocomposites were tested on HeLa (cervical carcinoma), A549 (lung cancer), and HDF (human dermal fibroblast) cells using MTT and colony formation assays. Our results indicate that cell viability is significantly inhibited in both cancer cell types with an IC50 value of 2 mg/mL especially in A549 cells, while 10 mg/mL in HDF cells. Nanocomposites significantly inhibited colony formation in both cancer cell lines, particularly in the HeLa cell line. The data indicated an inverse correlation between clay content in the copolymer complex and cell viability. The copolymer complex without clay had no negative impact on the cells. These findings suggest organo-clay nanocomposites as promising candidates for anticancer drug research.